2014
DOI: 10.1186/1471-2180-14-95
|View full text |Cite
|
Sign up to set email alerts
|

The non-metabolizable glucose analog D-glucal inhibits aflatoxin biosynthesis and promotes kojic acid production in Aspergillus flavus

Abstract: BackgroundAflatoxins (AFs) are potent carcinogenic compounds produced by several Aspergillus species, which pose serious threats to human health. As sugar is a preferred carbohydrate source for AF production, we examined the possibility of using sugar analogs to inhibit AF biosynthesis.ResultsWe showed that although D-glucal cannot be utilized by A. flavus as the sole carbohydrate source, it inhibited AF biosynthesis and promoted kojic acid production without affecting mycelial growth when applied to a glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 48 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…In this study, the use of S. roseolus simultaneously reduced the AFB 1 and KA concentrations. On the contrary, other authors observed a reduction in the AFB 1 concentration with an increase in the KA concentration by using D-glucal, C18:3 fractions, and dioctatin-A [ 25 , 26 , 27 ]. These results suggest the production of A. flavus secondary metabolites depends on the used agent.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, the use of S. roseolus simultaneously reduced the AFB 1 and KA concentrations. On the contrary, other authors observed a reduction in the AFB 1 concentration with an increase in the KA concentration by using D-glucal, C18:3 fractions, and dioctatin-A [ 25 , 26 , 27 ]. These results suggest the production of A. flavus secondary metabolites depends on the used agent.…”
Section: Discussionmentioning
confidence: 90%
“…S1 B , S2 B , S3 B ). Because the growth and aflatoxin biosynthesis could be affected by different carbon sources in Aspergillus ( 19 , 22 , 61 63 ), we next sought to assess whether aflatoxin biosynthesis would be affected by the improved media using TLC analysis. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Simple sugars (e.g., sucrose, glucose, fructose, sorbitol) used as carbon sources have been correlated with higher levels of AF production in A. flavus, A. parasiticus and A. nidulans [29,[96][97][98]. However, the use of D-glucal (a glucose-derivative not metabolized by fungi), used as the main source of sugar in the culture medium, inhibited AFB1 production [99].…”
Section: Nutrient Sources Carbon Sourcementioning
confidence: 99%